Intertextuality in Slovak Postmodern Prose. The Forms ofintertextual Connection in Dušan Dušek's Work Ponožky pred odletom/ Socks before Taking off - Adriana Porížeková (Slovenska Literatura, 2016)
The goal of the paper is to demonstrate the postmodern nature of Dušan Dušek´s collection of short stories named Ponožky pred odletom /Socks before Taking off/. The literary critical analysis of the collection in question has support and scientific basis in literary scientific works written by Tibor Žilka, who is the one among the other Slovak authors that has described the area of research in most detail. The scientific study shows that currently the latest book by Dušan Dušek implements the features of a postmodern text and can be classified by Tibor Žilka´s standards as the palimpsest type of prose. The central characteristic of Postmodernism as well as Dušek´s collection becomes intertextual connection achieved by intertextuality and metatextuality. The short stories include a number of quotations from folklore, newspapers, books by well-known writers as well as family members. The individual quotes are not excluded sentences, rather they are incorporated in the whole context, and form its inseparable part due to the fact that they complement the narrator´s (author´s) thoughts and memories. The other type of intertextual connection employed by the author and proving the postmodern nature of the short proses is metatextuality effectively used in various ways, in particular: by commenting on the litrary text itself, by putting a character in the text, or by quoting the writer´s own literary texts published earlier. The contribution of the paper can be seen in repeatedly showing and highlighting the characteristic of Postmodernism, i.e. intertextual connection and its practical application to the collection mentioned above.